Debt Relief and Adjustment Incentives : A Theoretical Exploration. (IMF Working Papers; Working Paper, 1988)
The purpose of this paper is to analyze the argument that debt relief would increase the incentive of a debtor country to make an adjustment effort (to invest) and that for this reason creditors may benefit by granting relief. It is shown that there are actually opposing incentive effects of debt relief and that the argument could be valid in particular circumstances. A distinction is made between exogenous and endogenous relief, the latter compelled by low capacity to pay caused by low investment earlier.